Sobrevivencia y crecimiento inicial en altura y diámetro de plántulas de Brosimum utile (Kunth) “Chingonga” en diferentes sustratos orgánicos en vivero. Puerto almendra, loreto, perú – 2023 - Chung Guzmán, Joejou Joseph (2024)
The general objective of the study was to determine the survival and initial growth in height and diameter of Brosimum utile (Kunth) “chingonga” seedlings in different organic substrates in the nursery, Puerto Almendra, Loreto, Peru – 2023. Four organic substrates as treatments: 30% chicken manure + 30% natural soil + 30% decomposed sawdust + 10% sand; 40% chicken manure + 40% decomposed sawdust + 20% sand; 80% chicken manure + 20% sand and 80% decomposed sawdust + 20% sand; the control was 100% natural soil. The survival and growth in height and diameter of the Brosimum utile (Kunth) “chingonga” seedlings were evaluated. The results indicate that the greatest increase in height occurred in treatment t2 (40% chicken manure + 40% decomposed sawdust + 20% sand) with 7,4 centimeters; Likewise, the greatest increase in diameter occurred in treatment t4 (80% decomposed sawdust + 20% sand) with 1.5 millimeters; The largest number of live plants (survival) was found in the control t0 (plants planted in 100% natural soil) with 60% of individuals. According to the statistical analysis, there is no significant difference in the increase in height and diameter; but there is a significant difference in the survival of the seedlings with 95% confidence.